Bionomía de los simúlidos (Diptera: Simuludae) en Costa Rica. IV. Localización y descripción de los lugares de recolección - Vargas V., Mario (1973)
Distribution and bionomics of black flies were studied in 100 strearns in Costa Rica. These streams were c1assified in four categories based on the nature of the strearn beds, turbulence, speed of water flow and to some extent on the arnount of trailing vegetation. The water temperature in the 100 streams varied from 9 C to 28 C. Five of the streams had 'an annual temperature range of only 1 C; the most coromon range was 4 C t0 9 C.No strong correlations were found with either larvae Ol biting adults and the ecological factors. In general, larval populations were higher in the lower altitudes, the fast turbulent strearns, the partially shaded and the polluted streams. About half the streams showed varying degrees of pollution and with the exception of two, the highest larval populations were in the most polluted streams. The two exceptions were strearns grossly polluted with the pulp of coffee bean hulls where the larval populations disappeared while the pulp was present in large arnounts. The biting adults were most numerous in the lower altitudes, near moderately fast and turbulent strearns, near unshaded streams and near streams with no obvious to líght pollution.